Microbial communities in the respiratory tract of patients with interstitial lung disease. Issue 12 (14th August 2013) - Garzoni, Christian; Brugger, Silvio D; Qi, Weihong; Wasmer, Sarah; Cusini, Alexia; Dumont, Philippe; Gorgievski-Hrisoho, Meri; Mühlemann, Kathrin; von Garnier, Christophe; Hilty, Markus
Abstract : Background: Molecular methods based on phylogenetic differences in the 16S rRNA gene are able to characterise the microbiota of the respiratory tract in health and disease. Objectives: Our goals were (1) to characterise bacterial communities in lower and upper airways of patients with interstitial lung disease (ILD) and (2) to compare the results with the microbiota of patients with Pneumocystis pneumonia (PCP) and normal controls. Methods: We examined the upper and lower respiratory tract of 18 patients with ILD of whom 5, 6, and 7 had idiopathic interstitial pneumonia (IIP), non-IIP and sarcoidosis, respectively. In addition, six immune-compromised patients with PCP and nine healthy subjects were included as controls. Exclusion criteria were recent bacterial/viral respiratory tract infection, HIV-positivity and subjects receiving antibiotic therapy. Bronchoalveolar lavage fluid and oropharyngeal swabs were simultaneously collected, and microbiota was characterised by ultra-deep 16S rRNA gene sequencing. Results: The microbiota in lower airways of the majority of patients (30; 90%) primarily consisted of Prevotellaceae, Streptococcaceae and Acidaminococcaceae. α and β diversity measurements revealed no significant differences in airway microbiota composition between the five different groups of patients. Comparison of bacterial populations in upper and lower respiratory tract showed significant topographical discontinuities for 7 (23%) individuals. Conclusions: IIP, non-IIP and sarcoidosis are not associated with disordered airway microbiota and a pathogenic role of commensals in the disease process is therefore unlikely. Nevertheless, molecular analysis of the topographical microbiota continuity along the respiratory tract may provide additional information to assist management of individual patients.